Chrysophycean stomatocysts from the Aershan Geological Park (Inner Mongolia), China - Pang, Wanting; Wang, Quanxi (Phytotaxa, 2014)
The Aershan National Geological Park (46–47° 39’ N, 119–121° 28’ E) characterized by volcanic landforms clusters is situated in south-west of the Great Xing’an Mountains. The investigation of chrysophycean stomatocysts was carried out based on sampling five times in this area. 171 morphotypes which were observed using scanning electron microscopy were identified and described in accordance with the guidelines of International Statospore Working Groupm (ISWG), 73 of them are new to science. It is hard to compare the stomatocysts community with that of other areas for the large number of unknown morphotypes, which indicated that amounts of study of stomatocysts morphology should be done in the whole Great Xing’an Mountains.